Linear Essential Spectrum Compressors (European Journal of Pure and Applied Mathematics, 2017)
Let $A$ be a unital $C^{*}$-algebra of real rank zero and $B$ be aunital semisimple complex Banach algebra. We characterize linearmaps from $A$ onto $B$ that compress different essential spectralsets such as the (left, right) essential spectrum, thesemi-Fredholm spectrum, and the Weyl spectrum. Essentiallyspectrally bounded linear mapping from $A$ onto $B$ are alsocharacterized.